Housing conditions as a social determinant of low birthweight and preterm low birthweight - Mario Vianna Vettore; Silvana Granado Nogueira da Gama; Gabriela de Almeida Lamarca; Arthur Orlando Corrêa Schilithz; Maria do Carmo Leal (Universidade de São Paulo, 2010)
OBJECTIVE: To assess the relationship between housing conditions and low birthweight and preterm low birthweight among low-income women. METHODS: A case-control study was conducted with post-partum women living in the city of Rio de Janeiro, Southeast Brazil, in 2003-2005. Two groups of cases, low birthweight (n=96) and preterm low birthweight infants (n=68), were compared against normal weight term controls (n=393). Housing conditions were categorized into three levels: adequate, inadequate, and highly inadequate. Covariates included sociodemographic and anthropometric characteristics, risk behaviors, violence, anxiety, satisfaction during pregnancy, obstetric history and prenatal care. RESULTS: Poor housing conditions was independently associated with low birthweight (inadequate - OR 2.3 [1.1;4.6]; highly inadequate - OR 7.6 [2.1;27.6]) and preterm low birthweight (inadequate - OR 2.2 [1.1;4.3]; highly inadequate - OR 7.6 [2.4;23.9]) and factors associated with outcomes were inadequate prenatal care and previous preterm birth. Low income and low maternal body mass index remained associated with low birthweight. CONCLUSIONS: Poor housing conditions were associated with low birthweight and preterm low birthweight.